Liang hua jin rong R yu yan gao ji jiao cheng = Mastering R for quantitative finance / = Mastering R for quantitative finance - Berlinger, Edina (Ren min you dian chu ban she = Posts & Telecom Press, 2017)
Detailed summary in vernacular field only.
880-05;Ben shu you Yingguo Packt Publishing gong si shou quan Ren min you dian chu ban she chu ban
Keywords: Finance -- Mathematical models -- Data processing; Finance -- Computer programs; R (Computer program language); Finances; Modèles mathématiques; Informatique; R (Langage de programmation)